2050 China : Becoming a Great Modern Socialist Country - Hu, Angang; Yan, Yilong; Tang, Xiao; Liu, Shenglong (Springer Nature, 2021)
This book is open access under a CC BY-NC-ND 4.0 license. This book is arranged and developed around the theme of (3z(B2050 China,(3y (Bit analyzes the factors and advantages of the Chinese road to socialist modernization, explores and summarizes the development goal and the basic logic of the socialist modernization of China, and further shows the general basis of the primary stage of socialism. According to the report delivered at the 19th Party Congress, and according to the (3z(Btwo-stage(3y (Bstrategic plan, this book looks ahead in detail to the overarching objective and sub-objectives of essentially achieving socialist modernization by 2035, discusses the building of a great modern socialist country in all respects from the perspective of the Party$1 (Bs six-sphere integrated plan of economic, political, cultural, social, ecological civilization, and national defense construction, and provides policy proposals. This book also analyzes the influence and the effect of the socialist modernization with Chinese characteristics on the world and it further presents the third centenary goal. In conclusion, this book is an elaboration of the work of the Institute for Contemporary China Studies, Tsinghua University. It reflects the intellectual innovation in the authors$1 (Bresearch on contemporary China, as well as the authors$1 (Bforesight and predictions about China$1 (Bs future development.s
English
Keywords: Politics & government; Political structure & processes; Development studies; Asian Politics; Governance and Government; Development Studies; socialist modernization; China 2050; Chinese characteristics; six-sphere integrated plan; Contemporary China Studies; Open Access; Politics & government; Asia; Political structure & processes